Analisis Penerapan Akuntansi Pajak Penghasilan Pasal 21 dan Pasal 23 Pada PT Perdana Dinamika Persada (PT.PDP) Banda Aceh - Muhajir Muhajir; Novi Mailidarni; Aliamin Aliamin; Eva Susanti (Akbis: Media Riset Akuntansi dan Bisnis, 2026)
This study aims to analyze the implementation of Income Tax Accounting Article 21 and Article 23 at PT. Perdana Dinamika Persada (PT.PDP) Banda Aceh. The research method used is descriptive qualitative with a case study approach. Data were obtained through interviews, observations, and documentation from the company. The results show that PT.PDP has implemented the withholding, payment, and reporting of Income Tax Article 21 in accordance with the applicable regulations, namely based on the Harmonization of Tax Regulations Law Number 7 of 2021. Similarly, Income Tax Article 23 is applied to transactions of professional services, technical services, and equipment rental with a tariff of 2% of the gross amount, and reporting is carried out through the e-Bupot DJP Online system. However, there are still challenges such as limited understanding of financial staff regarding the latest regulations and the need for a more automated recording system. This research is expected to contribute to the company in improving tax compliance and efficiency.